Macro-mineral concentrations in soil and forage in three grassland sites at Zacatecas - M. Márquez Madrid; H. Gutiérrez Bañuelos H.; R. Bañuelos Valenzuela; A. Muro Reyes; R.D. Valdez Cepeda (Revista Mexicana de Ciencias Pecuarias, 2017)
Mineral concentration in forage is an important factor for extensive livestock production. Therefore, a study was performed in order to evaluate the soil mineral contents and their relationships with forage mineral concentrations taking into account three grassland sites located at Zacatecas state, México. Soil organic matter (OM) content and pH as well as soil and forage contents of Ca, P, Mg, Na and K were estimated. Soil OM contents were not different (P>0.05) among sites averaging 2.99 %. Soil pH of site 2 was higher (P£0.05) than those of sites 1 and 3. Soil of site 2 had higher P, Ca and Mg concentrations than the minimum contents used as references. Soil contents of Na and K were lower than the reference contents suggesting deficiencies in all three sites. Considering requirements for growing cattle, P, Ca and Na were at insufficient levels in forage from all three sites. Significant correlations (r Pearson) suggest a positive effect of soil P content on forage P and Mg concentrations. Soil P content could affect forage Ca concentration and Ca:P ratio. Other correlations suggest soil Ca negative effects on forage Ca concentration and Ca:P ratio.